Product innovation and business sustainability of MSMEs: The role of competitive advantage and gender - Hunik Sri Runing Sawitri; Asri Laksmi Riani; Suryandari Istiqomah; Anastasia Riani Suprapti; Intan Novela Qurrotul Aini; Mugi Harsono (Journal of Innovation in Business and Economics, 2026)
This study investigates how product innovation influences the business sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, considering competitive advantage as a mediating variable and gender as a moderating variable. Drawing on the Resource-Based View (RBV), the study posits that innovation acts as a strategic internal capability that strengthens competitive advantage and long-term business survival. Data were collected from 91 MSME owners in the Solo Raya region through online and offline surveys and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that product innovation significantly enhances competitive advantage and business sustainability. Competitive advantage also directly and indirectly contributes to sustainability, confirming its mediating role in the innovation–sustainability relationship. However, gender does not moderate this relationship, indicating that innovative capability and sustainability outcomes are not inherently gendered. These findings highlight the importance of continuous innovation and strategic differentiation for MSME resilience in volatile post-pandemic markets, while emphasizing the need for inclusive policies to ensure equal access to innovation resources for all entrepreneurs.